Exploring ESL lecturers perspectives on the English preparatory course under the MDAB programme / Gurnam Kaur Sidhu … [et al.] - Kaur Sidhu, Gurnam; Chan, Yuen Fook; Lim, Peck Choo; Mohd Azkah, Siti Hajar Aishah (Penerbit UiTM (UiTM Press), 2016)
The Mengubah Destini Anak Bangsa (MDAB) pre-diploma English preparatory course is a course offered in Universiti Teknologi MARA (UiTM) which caters for under privileged Malay and Bumiputera students. The main aim of the course is to upgrade the English proficiency levels of these students to help them further their studies at diploma level. Having good English language skills is important in the 21st century. Hence, tertiary students should have good English skills to be successful in the 21st century. This paper investigates the ESL lecturers 'perceptions of the MDAB English Preparatory course. The study involved a total of 18 lecturers from three zones in UiTM Malaysia, namely the Central zone (Negeri Sembilan), the South zone (Malacca) and the North zone (Kelantan). Data were collected using semi-structured interviews. The findings showed that the lecturers felt that the current six contact hours is not sufficient to cover the English language components in the syllabus. Moreover, they felt that there were far too many assessments in the course which needed to be carried out during this six hour course. This further compounded their problems with regard to time constraints. Besides that, they felt that there was too much emphasis on the listening and speaking skills. These findings suggest that there is a need for an increase in the contact hours for the MDAB English Preparatory Course.